Pengaruh Model Pembelajaran Window Shopping Terhadap Kemampuan Menulis Teks Eksposisi Siswa Kelas X SMAS Budisatrya Medan - Martha Juliana Marpaung; Malan Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Indonesian language subjects consist of several subjects that require students to be able to write, one of which is writing expository texts. The student participants had problems in writing material, especially writing expository texts, which was proven by the average score which was still not optimal. The formulation of the problem raised in this research is how the window shopping type cooperative learning model influences the ability to write expository texts of class X students at Budisatrya Medan Private High School. This research aims to determine the effect of the window shopping type cooperative learning model on the ability to write expository texts of class X students at Budisatrya Medan Private High School. This research is a type of quantitative research using experimental methods, a research method used to determine the effect of a treatment on the characteristics of the subjects studied. The data collection techniques used in this research were observation techniques, interview techniques and test techniques, with data sources consisting of 35 students. Based on data analysis, it can be concluded that: The window shopping type cooperative learning model has an influence on the ability to write expository texts in class This can be seen and proven by the average post-test results for the control class being 69.857 with the average post-test results for the experimental class being 85.